2020
DOI: 10.1001/jamapediatrics.2020.1990
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Meningococcal Disease Before and After Implementation of Quadrivalent Meningococcal Conjugate Vaccine in the United States

Abstract: IMPORTANCEIn 2005, the US Advisory Committee on Immunization Practices recommended routine quadrivalent meningococcal conjugate (MenACWY) vaccine for all adolescents aged 11 to 12 years, and in 2010, a booster dose for adolescents aged 16 years. Measuring the association between MenACWY vaccination and the incidence of meningococcal disease in adolescents is critical for evaluating the adolescent vaccination program and informing future vaccine policy.OBJECTIVE To describe the association between MenACWY vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Measuring the association between adolescent MenACWY vaccination on rates of meningococcal disease has been challenging because of the low and decreasing incidence of meningococcal disease among all age groups. However, from MenACWY introduction through 2017, adolescents experienced the greatest percentage decreases (>90%) in meningococcal disease incidence due to serogroups C, W, or Y combined compared with other age groups (179). In the setting of 85% coverage with at least 1 dose of MenACWY-D or MenACWY-CRM among U.S. adolescents aged 13-17 years and 44% coverage with at least 2 doses among adolescents aged 17 years by 2017, a twofold to threefold increase in the rate of decline in incidence was observed during the postvaccination period compared with the prevaccination period among adolescents, suggesting that vaccination with MenACWY-D or MenACWY-CRM is associated with reductions in disease rates in adolescents (179,180).…”
Section: Vaccination and Meningococcal Disease Incidencementioning
confidence: 99%
“…Measuring the association between adolescent MenACWY vaccination on rates of meningococcal disease has been challenging because of the low and decreasing incidence of meningococcal disease among all age groups. However, from MenACWY introduction through 2017, adolescents experienced the greatest percentage decreases (>90%) in meningococcal disease incidence due to serogroups C, W, or Y combined compared with other age groups (179). In the setting of 85% coverage with at least 1 dose of MenACWY-D or MenACWY-CRM among U.S. adolescents aged 13-17 years and 44% coverage with at least 2 doses among adolescents aged 17 years by 2017, a twofold to threefold increase in the rate of decline in incidence was observed during the postvaccination period compared with the prevaccination period among adolescents, suggesting that vaccination with MenACWY-D or MenACWY-CRM is associated with reductions in disease rates in adolescents (179,180).…”
Section: Vaccination and Meningococcal Disease Incidencementioning
confidence: 99%
“…A potential limitation of this analysis is that assumptions for MenABCWY vaccination coverage rely on historical data for individual MenB and MenACWY vaccines [9,10,13,[19][20][21]23,26,[28][29][30][31][32][33][34][35][36]59]. There are some hSBA data showing that sera from MenB-vaccinated adolescents have bactericidal activity against non-serogroup B meningococcal strains [60]; however, the majority of the benefit from a MenABCWY vaccine would likely stem from the highly efficacious protection provided by the MenACWY conjugate component [61][62][63]. Definitive estimates of vaccine efficacy await clinical trials and real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…Mbaeyi et al demonstrated that even if infants <1 year of age have experienced the greatest absolute decline in disease incidence due to serogroups C, W, and Y, adolescents aged 11–15 years have shown the greatest percentage decrease in disease incidence due to serogroups C, W, and Y during the post-vaccination period (a 67.0% reduction in the disease incidence during the post-primary dose period; 88.8% during the post-booster dose period) [ 42 ].…”
Section: Vaccinesmentioning
confidence: 99%